PERAN SIFAT TANAH AWAL DALAM PERUBAHAN SIFAT KIMIA TANAH SULFAT MASAM AKIBAT APLIKASI JERAMI PADI - s, Nurzakiah; A, Fahmi (Fakultas Pertanian Universitas Palangka Raya, 2020)
Tidal land is a swamp land which directly or indirectly affected by sea water tides. The overflow and intensity of tides or fluctuation of ground water levels strongly influence to the soil properties. This review is constructed to examine the role of native soil properties towards the changes in chemical properties of acid sulphate soils that occured due to organic matter application. This paper is a review of the data in the paper